Outlook of the automotive e-commerce in the US & evaluation of a business idea - LowMiles - Sagols, Michael; Tyll, Ladislav; Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
This Bachelor’s thesis provides information about online used car retailers in the United States and provides insight on how to enter the market by providing e-commerce capabilities to traditional dealerships as a pre-seed venture. This thesis is divided into the theoretical section and the practical section. The theoretical section provides background on how to design a business model and business plan. It includes various strategic tools and frameworks. The practical section is where the business model and business plan described in the theoretical section are applied.
Vedoucí práce: Ladislav Tyll
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses